The Design Features, Quality by Design Approach, Characterization, Therapeutic Applications, and Clinical Considerations of Transdermal Drug Delivery Systems-A Comprehensive Review - Durgaramani Sivadasan; Osama A. Madkhali (MDPI AG, 2024)
Transdermal drug delivery systems (TDDSs) are designed to administer a consistent and effective dose of an active pharmaceutical ingredient (API) through the patient's skin. These pharmaceutical preparations are self-contained, discrete dosage forms designed to be placed topically on intact skin to release the active component at a controlled rate by penetrating the skin barriers. The API provides the continuous and prolonged administration of a substance at a consistent rate. TDDSs, or transdermal drug delivery systems, have gained significant attention as a non-invasive method of administering APIs to vulnerable patient populations, such as pediatric and geriatric patients. This approach is considered easy to administer and helps overcome the bioavailability issues associated with conventional drug delivery, which can be hindered by poor absorption and metabolism. A TDDS has various advantages compared to conventional methods of drug administration. It is less intrusive, more patient-friendly, and can circumvent first pass metabolism, as well as the corrosive acidic environment of the stomach, that happens when drugs are taken orally. Various approaches have been developed to enhance the transdermal permeability of different medicinal compounds. Recent improvements in TDDSs have enabled the accurate administration of APIs to their target sites by enhancing their penetration through the stratum corneum (SC), hence boosting the bioavailability of drugs throughout the body. Popular physical penetration augmentation methods covered in this review article include thermophoresis, iontophoresis, magnetophoresis, sonophoresis, needle-free injections, and microneedles. This review seeks to provide a concise overview of several methods employed in the production of TDDSs, as well as their evaluation, therapeutic uses, clinical considerations, and the current advancements intended to enhance the transdermal administration of drugs. These advancements have resulted in the development of intelligent, biodegradable, and highly efficient TDDSs.